THE EFFECT OF ZISWAF, ROE, AND GWM FUND RECEIPTS ON NPF NETT WITH FIRM SIZE AS A MODERATION VARIABLE IN ISLAMIC BANKING IN INDONESIA PERIOD 2018.Q1-2023.Q3 - Istiqomah, Azizatul; Budianto, Eka Wahyu Hestya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The effect of ZISWAF funds, ROE, and GWM on NPF nett using firm size moderation is a complex research subject and requires further analysis. This study found that ZISWAF funds have a positive influence on community welfare, as well as an effect on NPF nett indirectly through community development and education. ROE and reserve requirements also have an influence on NPF nett, but research needs to be expanded to fully understand their influence. Firm size plays an important role in moderating the effect of various financial factors on firm performance, as well as influencing the relationship between ZISWAF funds, ROE, and GWM with NPF nett. Further research is needed to fully understand the effect of ZISWAF funds, ROE, and GWM on NPF nett, as well as expanding the parameters and scope of the study to broaden the knowledge of its effect on other sectors in various ASEAN countries.